Threats and Strategies for Personal Data Protection in Digital Services: A Thematic Review and Regulatory Analysis - Djayanti; Silalahi, Wilma (APPS Publications, 2025)
This article aims to analyze the threats to personal data in digital services and the protection strategies used, by integrating legal, policy, information technology, and digital literacy approaches. This research uses a qualitative approach based on doctrinal, thematic, and comparative analysis. Data was collected from legal texts, policy documents, academic literature, and empirical studies to build a comprehensive analytical framework. The analysis was conducted to identify threat categories and protection strategies, and evaluate the effectiveness of regulatory frameworks such as the General Data Protection Regulation (GDPR) and the PDP Law. The research found that threats to personal data stem from both technical (phishing, malware, dark patterns) and non-technical factors (low digital literacy, weak regulation). An effective protection strategy is the integration of technical approaches such as encryption and digital auditing, as well as non-technical approaches such as education, regulation, and institutional transparency. This study distinguishes itself from previous literature by combining legal, technological, and social analysis in a unified synthesis, and provides a review of the effectiveness of the PDP Law as a public protection instrument.